Dual Antimelanogenic Effect of Nicotinamide-Stabilized Phloretin Nanocrystals in Larval Zebrafish - Yixuan Li; Hong Xiang; Xinyue Xue; Yilan Chen; Zhiyuan He; Zhongrui Yu; Li Zhang; Xiaoqing Miao (MDPI AG, 2022)
Melanin is a kind of dark insoluble pigment that can cause pigmentation and free-radical clearance, inducing melasma, freckles, and chloasma, affecting the quality of life of patients. Due to poor water solubility and low safety, the absorption of poorly water-soluble drugs is limited by the hinderance of a skin barrier. Therefore, it is necessary to develop new, safe, and highly efficient drugs to improve their transdermal absorption efficiency and thus to inhibit the production of melanin. To address these issues, we developed a new nicotinamide (NIC)-stabilized phloretin nanocrystals (PHL-NCs). First, NC technology significantly increased the solubility of PHL. The in vitro release results indicated that at 6 h, the dissolution of the PHL-NIC-NCs was 101.39% ± 2.40% and of the PHL-NCs was 84.92% ± 4.30%, while that of the physical mixture of the two drugs was only 64.43% ± 0.02%. Second, NIC acted not only as a stabilizer to enlarge the storage time of PHL-NIC-NCs (improved to 10-day in vitro stability) but also as a melanin transfer inhibitor to inhibit melanin production. Finally, we verified the melanin inhibition effect of PHL-NIC-NCs evaluated by the zebrafish model. It showed that 0.38 mM/L PHL-NIC-NCs have a lower tyrosinase activity at 62.97% ± 0.52% and have less melanin at 36.57% ± 0.44%. The inhibition effect of PHL-NCs and PHL-NIC-NCs was stronger compared to the positive control arbutin. In conclusion, the combination of NIC and PHL achieves better inhibition of tyrosinase and inhibition of melanin production through synergism. This will provide a direction to the subsequent development of melanin-inhibiting drugs and the combined use of pharmaceutical agents.